On Earth as it is in Heaven : Cultivating a Contemporary Theology of Creation - Meconi, David Vincent (Book collections on Project MUSE., 2021)
"With the 2015 publication of Pope Francis's encyclical Laudato Si', many people of faith have found themselves challenged to seek new ways of addressing serious ecological questions -- issues essential to the flourishing of all creatures and not just human beings. This volume brings together fifteen select scholars to consider pressing contemporary environmental concerns through the lens of Catholic theology. Drawing from the early church fathers and other authoritative voices in the Christian tradition, the contributors to On Earth as It Is in Heaven show how ancient, creedal Christianity offers significant insights into our current ecological dilemmas and speaks powerfully about what it means for us today to care well for God's good creation."--